1
$\begingroup$

I'm going over the proof for the Final Value theorem using the Dominated Convergence theorem on Wikipedia, I don't understand how from the equation

$$sF\left(s\right)=\int_{0}^{\infty}f\left(\frac{t}{s}\right)e^{-t}dt$$

and the fact that $\left|f\left(\frac{t}{s}\right)e^{-t}\right|$ is dominated by $Me^{-t}$ they get to the limit

$$\lim_{s\searrow0}sF\left(s\right)=\int_0^{\infty}{\alpha}e^{-t}dt=\alpha$$

$\endgroup$
1
$\begingroup$

$\newcommand{\dd}{\mathrm{d}}\newcommand{\R}{\mathbb{R}}\newcommand{\C}{\mathbb{C}}\newcommand{\lap}{\mathscr{L}}$I went through the proof again, and I think that you're right. The variables are intertwined and the proof is not rigorous. Here's the correct statement:

Final value theorem. Suppose that the following conditions are satisfied:

  1. $f$ is continuously differentiable and both $f$ and $f'$ have a Laplace transform
  2. $f'$ is absolutely integrable, that is, $\int_0^\infty|f'(\tau)|\dd\tau$ is finite,
  3. $\lim_{t\to\infty}f(t)$ exists and is finite,

Then,

\begin{equation} \lim_{t\to \infty}f(t) = \lim_{s\to 0^+}sF(s). \end{equation}

Proof. We know that the Laplace transform of the derivative is

\begin{equation} sF(s) - f(0^+) {}={} \lap\{f'(t)\}(s) {}={} \int_{0^+}^\infty f'(\tau) e^{-s\tau}\dd\tau. \end{equation} Therefore, \begin{align} \lim_{s\to 0^+} sF(s) {}={}& f(0^+) + \lim_{s{}\to{}0^+} \int_{0^+}^{\infty}f'(\tau)e^{-s\tau}\dd\tau \notag \end{align}

We want to use the dominated convergence theorem ; Define $\phi_s(\tau) = f'(\tau)e^{-s\tau}$. We have $|\phi_s(\tau)|\leq f'(\tau)$ which is assumed to be absolutely integrable (Assumption 2). Therefore,

\begin{align} \lim_{s\to 0^+} sF(s) {}={}&f(0^+) + \int_{0^+}^{\infty} \lim_{s{}\to{}0^+} f'(\tau)e^{-s\tau}\dd\tau \notag \\ {}={}&f(0^+) + \int_{0^+}^{\infty} f'(\tau)\dd\tau \notag \\ {}={}& {f(0^+)} + \lim_{t\to\infty}f(t) - {f(0^+)}, \\ {}={}& \lim_{t\to\infty} f(t). \end{align} This completes the proof. $\Box$

Comment on the Wikipedia article (8 May, 2019): it is stated that with a change of variables, $\xi = st$, (in fact, the same symbol is used for $t$ and $\xi$), the integral becomes

$$ \int_0^\infty \lim_{s\to 0^+}f(\xi/s) e^{-\xi}\dd\xi. $$

As the OP noted, there is some confusion in that proof; in fact, $\xi$ and $s$ are not independent variables (by definition), so the limit $\lim_{s\to 0^+}f(\xi/s)$ is not equal to $\lim_{t\to\infty}f(t)$.

$\endgroup$
  • $\begingroup$ How did you make the step $\int_0^{\infty}\lim_{s\to 0^+} f\left(\frac{\xi}{s}\right)e^{-\xi}d\xi = \lim_{s\to 0^+} f\left(\frac{\xi}{s}\right)\int_0^{\infty}\lim_{s\to 0^+}$ if the limit depends on $\xi$? $\endgroup$ – SIMEL May 8 at 16:16
  • $\begingroup$ @SIMEL Thank you for accepting my answer. Let me rewrite it in a more clear way. I'll also add the statement of FVT for completeness. $\endgroup$ – Pantelis Sopasakis May 8 at 16:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.